2013
DOI: 10.1016/j.neuroimage.2012.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal shape variations at term equivalent age in very preterm infants compared with term controls: Perinatal predictors and functional significance at age 7

Abstract: The hippocampus undergoes rapid growth and development in the perinatal months. Infants born very preterm (VPT) are vulnerable to hippocampal alterations, and can provide a model of disturbed early hippocampal development. Hippocampal shape alterations have previously been associated with memory impairment, but have never been investigated in infants. The aims of this study were to determine hippocampal shape differences between 184 VPT infants (<30 weeks’ gestation or <1250 g at birth) and 32 full-term infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 67 publications
3
61
0
1
Order By: Relevance
“…The VLBW adults with the largest hippocampi had the highest scores in all indices of the WMS-III. This is in agreement with a study by Thompson et al (2013) who investigated volume and shape variations of the hippocampi measured at term-equivalent age (TEA) and memory function at age 7 in very preterm born children . They also reported a positive association between hippocampal volume and memory.…”
Section: Relationship Between Volumes Of the Hippocampi And Memory Prsupporting
confidence: 92%
See 2 more Smart Citations
“…The VLBW adults with the largest hippocampi had the highest scores in all indices of the WMS-III. This is in agreement with a study by Thompson et al (2013) who investigated volume and shape variations of the hippocampi measured at term-equivalent age (TEA) and memory function at age 7 in very preterm born children . They also reported a positive association between hippocampal volume and memory.…”
Section: Relationship Between Volumes Of the Hippocampi And Memory Prsupporting
confidence: 92%
“…While some studies have shown reduced verbal memory in preterm born children (Taylor et al, 2000) and adolescents (Gimenez et al, 2004), others have not reported such difficulties (Narberhaus et al, 2007;Rushe et al, 2001) and studies are lacking in adult populations. The lower score in the Visual Delayed index than in the Auditory Delayed index among the VLBW young adults in our study may be related to increased vulnerability of the white matter in the visual system to hypoxic-ischemic injuries in preterm born subjects (Thompson et al, 2013). We have reported that reduced visual perceptual and visual-motor integration in the same VLBW study population at age 15 correlated to reduced white matter integrity in long association tracts evaluated with diffusion tensor imaging (Skranes et al, 2007).…”
Section: Memory Profilementioning
confidence: 50%
See 1 more Smart Citation
“…Smaller bilateral hippocampal volume in VPT samples compared with controls has been described at school‐age (~9% volume reduction),12, 13 adolescence (~14% volume reduction),14, 15 and adulthood16, 17 although some studies have found no hippocampal volume differences when correcting for factors such as intracranial volume 18, 19. Interestingly, hippocampal volume at term, but not at 7 years of age (or the amount of growth between these time‐points), has been associated with episodic memory abilities at age seven 12, 18, 20. This suggests that children with early hippocampal damage may have a limited capacity for the development of episodic memory functions.…”
Section: Episodic Memorymentioning
confidence: 99%
“…111 In contrast, white matter myelination is still evolving and hippocampal indices are profoundly affected by immaturity and prematurity. 112 Development of practical methods for assessing tissue stores in patients requiring long-term parenteral nutrition. 14,115 Research and development of appropriate monitoring strategies for other trace element and vitamin deficiencies and toxicities in patients given parenteral nutrition.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%